EFL TEACHERS’ VIEWS TOWARDS THE NEED OF EVALUATING ENGLISH LANGUAGE TEACHING (ELT) TEXTBOOKS FOR CLASSROOM INSTRUCTION - Kodriyah, Lailatul; Albakri , Intan Safinas Mohd Ariff; Hakim, Arif Rahman (Jurnal Review Pendidikan dan Pengajaran, 2024)
In EFL country, the use of the textbook in the classroom is essential. Teachers and students rely heavily on the textbook in order to learn English. Since the flourishing of the English language textbook in the country, the teachers should make careful decision when selecting a textbook. Therefore, a process to evaluate an English textbook should be carried on. The purpose of the current study is to understand deeply about English teachers’ perceptions towards the needs of evaluating a textbook. Five English language teachers who have more than ten years of teaching experiences were involved in the study. Semi-structured interview which consisted of several questions was conducted in order to gather the data. The results indicated that most of English language teachers in Indonesia are currently not familiar with the textbook evaluation process. Even though most of them are not familiar with the textbook evaluation process, the findings from the interview showed that the teachers-respondents agreed evaluating a textbook is an important process during classroom instruction and it should be carried out before or after teaching session as it help the teachers to decide the materials selection.